Factors associated with functional capacity of elderly registered in the Family Health Strategy - Débora de Melo Trize; Marta Helena Souza de Conti; Márcia Aparecida Nuevo Gatti; Natasha Mendonça Quintino; Sandra Fiorelli Almeida Penteado Simeão; Alberto de Vitta (Fisioterapia e Pesquisa, 2014)
The objective of this study was to verify the level of functional capacity in subjects aged 60 years or older from the Family Health Strategy "Vila São Paulo", in Bauru, São Paulo State, Brazil, and its association with the sociodemographic, behavioral, ergonomic, and referred health variables. A cross-sectional study was conducted on 363 elderly selected by the two-stage cluster technique, who were interviewed at home using the multidimensional instrument (sociodemographic, behavioral, ergonomic, referred health information), the Nordic questionnaire, and Katz and Lawton scales. Descriptive, bivariate, and multivariate analyses by logistic regression were used. Results showed that 36.9% of elderly were dependent on daily life activities, whereas 51.0% were on instrumental daily life activities. It also indicated that functional disability in daily life activities was associated with age range, repetitive movements, sedentary lifestyle, number of diseases, and musculoskeletal pain, while years of study, repetitive movements, number of diseases and physical inactivity showed an association with decreased instrumental daily life activities. The identified characteristics that are related to disability for daily life activities and instrumental daily life activities suggest a complex causal network; therefore, preventive actions directed specifically to some factors are needed, providing benefits to the quality of life of elderly.